Characterization and expression analysis of the STAT pathway in anopheles dirus - Liew, Jonathan Wee Kent; Leong, Cherng Shii; Wong, Meng Li; Vythilingam, Indra; Fong, Mun Yik; Lau, Yee Ling (Faculty of Science, Chiang Mai University, 2018)
The Janus kinase-signal transducers and activators of transcription (JAK-STAT) pathway is one of the main signaling pathways mediating immune responses towards malaria parasites in Anopheles. Core components of the STAT pathway are STAT, suppressor of cytokine signaling (SOCS) protein, and protein inhibitor of activated STAT (PIAS) protein. However, this pathway is the least studied among the three major signaling pathways. Recent study found that Anopheles dirus lacks a second intronless STAT. The implication of this phenomenon is still unclear. Moreover, molecular understanding of An. dirus is scarce. Thus, the three components of the pathway were studied using an Anopheles dirus/Plasmodium berghei experimental model. The three proteins were sequenced and characterized. The STAT, PIAS and SOCS proteins exhibited high sequence similarity with those of other Anopheles. Nonetheless, there were no significant changes in the expression levels of the genes post Plasmodium berghei infection. The current study warrants further investigation on the JAK-STAT pathway in Anopheles. More investigations on the Anopheles spp. in different geographical regions should be pursued, to understand the possible differences in the JAK-STAT pathway among these Anopheles.